2021
DOI: 10.1016/j.ajogmf.2021.100458
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory analysis of symptomatic and asymptomatic pregnant patients with SARS-CoV-2 infection

Abstract: Background : Inflammatory biomarkers have been utilized to portend disease severity in non-pregnant individuals with SARS-CoV-2 infection. However, currently limited data are available, and with mixed results, to elucidate which inflammatory biomarkers may be most associated with clinical phenotype in pregnant patients. Objective : We aimed to compare laboratory findings among pregnant patients with severe acute respiratory syndrome coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the pregnancy correlation between abnormal LFTs and disease deterioration is scarce and inconsistent. Fisher SA et al revealed that transaminitis, elevated PCT and elevated LDH were independently associated with severe to critical disease compared to mild to moderate [ 36 ]. In another work written by Choudhary et al SARS-CoV-2 the infected pregnant women with liver dysfunction manifested in higher serum levels of ALT, AST and TBIL have been documented to experience heightened inflammation, more severe disease, increased morbidity, and higher mortality rates compared to those without liver impairment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the pregnancy correlation between abnormal LFTs and disease deterioration is scarce and inconsistent. Fisher SA et al revealed that transaminitis, elevated PCT and elevated LDH were independently associated with severe to critical disease compared to mild to moderate [ 36 ]. In another work written by Choudhary et al SARS-CoV-2 the infected pregnant women with liver dysfunction manifested in higher serum levels of ALT, AST and TBIL have been documented to experience heightened inflammation, more severe disease, increased morbidity, and higher mortality rates compared to those without liver impairment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the inflammatory syndrome associated with COVID-19 was also outlined in various studies on pregnant patients [ 37 , 38 , 39 ]. Moreover, it was demonstrated that elevated serum levels of procalcitonin and ferritin were associated with severe forms of disease [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic pregnant patients, compared to non-pregnant patients with COVID-19, are at increased risk of more severe illness due to COVID-19 including preeclampsia, preterm delivery, and maternal mortality [ 4 ]. Compared with non-pregnant age-matched women with COVID-19, parturients with severe COVID-19 in pregnancy are more likely to be admitted to the intensive care unit, require mechanical ventilation, or necessitate advanced respiratory and hemodynamic support, including extracorporeal membrane oxygenation (ECMO) [ 5 , 6 , 7 , 8 , 9 ]. Pregnant and postpartum patients who are Black or Hispanic, of advanced maternal age, or those with comorbidities including obesity, diabetes, hypertension and lung disease may be at even higher risk for severe COVID-19 infection, maternal death, and adverse perinatal outcomes including increased cesarean delivery and hypertensive disorders of pregnancy (HDP) [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%